Effects of different solvents on phytochemical constituents, in-vitro antimicrobial activity, and volatile components of Boehmeria rugulosa Wedd. wood extract - Priyanka Arya; Devina Vaidya; Manisha Kaushal; Sunita Devi; Anil Gupta; Subhash Chand (Scientific Reports)
Abstract This study investigates the effects of various solvents on the phytochemical composition, in-vitro antimicrobial activity, and volatile constituents of Boehmeria rugulosa Wedd. wood extract. Phytochemical screening revealed significant variations in the concentration of bioactive compounds depending on the extraction solvent. Methanolic, ethanolic, and aqueous extracts exhibited distinct profiles of alkaloids, flavonoids, phenolics, and tannins, with notable differences in their respective bioactive contents. Among the tested solvents, 70% aqueous ethanol yielded the highest extract recovery, containing total phenols (229.3 mg GAE/g) and total flavonoids (67.13 mg QE/g). Gas Chromatography-Mass Spectrometry (GC–MS) identified 14 volatile compounds, including terpenoids, aldehydes, ketones, and phenolic derivatives, with clear solvent-dependent variations. In-vitro antimicrobial assays indicated that the ethanolic extract exhibited the strongest antibacterial activity, while the aqueous extract showed moderate antifungal activity. The 70% aqueous ethanol extract demonstrated significant antibacterial efficacy against Staphylococcus aureus ATCC 12,600 (18.45 mm), Bacillus cereus ATCC 6633 (15.88 mm), and Escherichia coli ATCC 1041 (12.35 mm). These findings highlight the critical role of solvent polarity in optimizing the extraction of bioactive and antimicrobial compounds from B. rugulosa wood, with implications for the development of plant-based therapeutic agents and natural preservative systems.